Respuesta :

1. 3x+9-9=18-9      

3x=9

x=3

2. 4x-12=20

4x-12+12=20+12

4x=32

x=8

3. x+0-0

x=0

4. x/2-2+2=9+2

x/2=11

(2)(x/2)=11(2)

x=22

5. 12x-21=3

12x-21+21=3+21

12x=24

x=2

6. 3x-15=18

3x-15+15=18+15

3x=33

x=11

7. 3x-25=14

3x-25+25=14+25

x=13

8. 3x+16=22

3x+16-16=22-16

x=2

9. 2x-8=2

2x-8+8=2+8

2x=10

x=5

10. 9x-18=9

9x-18+18=9+18

9x=27

x=3

11. x+0=0

x=0

12. 9x-8=19

9x-8+8=19+8

9x=27

x=3

If  you want to check my answers

use substitution method by using the x into for each equation.

1. 3x + 9 = 18

3x + (9 - 9) = 18 - 9

3x = 9

(3x / 3) = 9/3  

X = 3

2. 4x - 12 = 20

4x + (-12+12) = 20 + 12

4x = 32

(4x / 4) = 32/4

X = 8

3. This one isn't really clear in the pic so if you write it in the comments again I can help

4. [tex]\frac{x}{2}[/tex]- 2 = 9

[tex]\frac{x}{2}[/tex]+(- 2+2) =( 9 + 2)

[tex]\frac{x}{2}[/tex] = 11

2([tex]\frac{x}{2}[/tex]) = (11)(2)

X = 22  

5. 12x -21 = 3

12x + (-21 + 21) = (3 +21)

12x = 24

12x/12 = 24 / 12

X = 2

6. 3x -15 = 18

3x + (-15 + 15) = 18 + 15

3x = 33

3x/3 = 33/3

X = 11

7. 3x - 25 = 14

3x + (-25 + 25) = 14 + 25

3x/3 = 39/ 3

X = 13  

8.  3x + 16 = 22

3x + (16 - 16) = 22 -16

3x = 6

3x/3 = 6/3

X = 2  

9. 2x - 8 = 2

2x + (-8 + 8) = 2 + 8  

2x/2 = 10/2

X = 5

10. 9x - 18 = 9

9x + (-18 + 18) = 9 + 18  

9x/9 = 27/9

X = 3

11. X + 0 = 0

X + (0-0) = 0-0

X = 0

12. 9x - 8 = 19

9x + (-8 + 8) = 19 + 8

9x/9 = 27/9

X = 3

I hope this makes sense and now you understand the process of doing this and can do it on your own!